A comparison of physiological responses between attached and pelagic populations of Sargassum horneri under nutrient and light limitation. (January 2022) - Bao, Menglin; Park, Ji-Sook; Wu, Hailong; Lee, Hyuk Je; Park, Sang Rul; Kim, Tae-Hoon; Son, Young Baek; Lee, Tae Hee; Yarish, Charles; Kim, Jang K.
Abstract: Large-scale Sargassum blooms have been increasingly observed in coastal zones in recent years. Sargassum horneri (Turner) C. Agardh blooms (pelagic) have been observed in Jeju Island (Korea) and the southwest of the Korean Peninsula, causing serious problems for seaweed and abalone farms as well as for fisheries, tourism and recreational industries. The present study explored the physiological responses of attached and pelagic S. horneri populations cultivated under different nutrient concentrations (HN: 50 μM of nitrogen and 5 μM of phosphorus; LN: 5 μM of nitrogen and 0.5 μM of phosphorus) and photosynthetically active radiation (PAR) (H-PAR: 250; M-PAR: 150; L-PAR: 50 μmol photons m −2 s −1 ) for 25 days. Relative growth rates (RGR) were significantly lower in the pelagic population than that in the attached population. All thalli from the pelagic population died within 20 days. Chlorophyll a and c, and carotenoids were significantly higher at HN than at LN, and decreased as PAR increased for both populations. For the attached population, photosynthetic rate, tissue nitrogen, and carbon and nitrogen removal were also significantly higher at HN than at LN. These results suggest that high nutrient and lower PAR increased the biomass accumulation of attached populations in coastal areas. Nutrient limitation and high PAR may accelerate senescence of the pelagic populations while traveling on the sea surface from their point of origin. Highlights: Attached population of Sargassum horneri (Turner) C. Agardh grew faster than pelagic population. High nutrients increased growth rate in both populations. In the attached population photosynthesis and tissue nitrogen increased with increasing levels of nutrients. High PAR decreased pigment content in both populations. High-PAR decreased growth rate but did not affect growth and photosynthesis of attached population.